Plague, Cattle Pestilence and Hunger in The Papal State (1713-1716): A Contribution to the History of Everyday Life from the Perspective of British Sources - Kocić, Marija V.; Elezović, Dalibor M.; Dajč, Haris E. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The British government did not appoint its representative in Rome, due to which its members in Venice were obliged to regularly inform about developments in the Papal States. For this reason, their reports contain data that reveal certain aspects of the daily life of the inhabitants of the Papal States, primarily those related to epidemics, hunger and natural disasters. Our research is based on the archival material and relevant histories of this era, as well as the contemporary results of historical science for comparative analysis and the creation of an objective scientific picture of the epidemics and other natural disasters that affected the inhabitants of the Papal States in this short period from the beginning of the 18th century.